Overcoming Behavioral Biases in Job Search : The Value of Action Planning - Carranza, Eliana; Pimkina, Svetlana (World Bank, Washington, DC, 2018)
Job search is a largely self-regulated process, subject to behavioralbiases that lead to sub-optimal search and employment outcomes.Within this context, we designed, implemented and tested anaction-planning tool to promote greater job search intensity.We find that action planning helps unemployed youths to follow through on their job search intentions, and adopt a more efficient and effective search strategy. Greater search efficiency and effectiveness translates to sizeable improvements in employment outcomes. Given that a rising number of young people globally are not enrolled in education, employed, or searching for work it is particularly important to understand how to optimize the job search process. There is suggestive evidence that in the presence of high and persistent unemployment, South African youth are becoming increasingly discouraged in their job search.